Agricultural land use and hydrology affect variability of shallow groundwater nitrate concentration in South Florida - Ritter, A; Muñoz-Carpena, R; Bosch, D.D; Schaffer, B; Potter, T.L (Hydrological processes, 2007)
South Florida's Miami-Dade agricultural area is located between two protected natural areas, the Biscayne and Everglades National Parks, subject to the costliest environmental restoration project in history. Agriculture, an important economic activity in the region, competes for land and water resources with the restoration efforts and Miami's urban sprawl. The objective of this study, understanding water quality interactions between agricultural land use and the shallow regional aquifer, is critical to the reduction of agriculture's potentially negative impacts. A study was conducted in a 4-ha square field containing 0·9 ha of corn surrounded by fallow land. The crop rows were oriented NW-SE along the dominant groundwater flow in the area. A network of 18 monitoring wells was distributed across the field. Shallow groundwater nitrate-nitrogen concentration [N-NO₃⁻] was analyzed on samples collected from the wells biweekly for 3 years. Detailed hydrological (water table elevation [WTE] at each well, groundwater flow direction [GwFD], rainfall) and crop (irrigation, fertilization, calendar) data were also recorded in situ. Flow direction is locally affected by seasonal regional drainage through canal management exercised by the local water authority. The data set was analyzed by dynamic factor analysis (DFA), a specialized time series statistical technique only recently applied in hydrology. In a first step, the observed nitrate variation was successfully described by five common trends representing the unexplained variability. By including the measured hydrological series as explanatory variables the trends were reduced to only three. The analysis yields a quantification of the effects of hydrological factors over local groundwater nitrate concentration. Furthermore, a spatial structure across the field, matching land use, was found in the five remaining common trends whereby the groundwater [N-NO₃⁻] in wells within the corn rows could be generally separated from those in fallow land NW and SE of the crop strip. Fertilization, masked by soil/water/plant-delayed processes, had no discernible effect on groundwater nitrate levels. Copyright © 2006 John Wiley & Sons, Ltd.